Working Conditions and Factory Survival: Evidence from Better Factories Cambodia - Raymond Robertson; Drusilla Brown; Rajeev Dehejia (Institute for the Study of Labor (IZA), 2016)
A large and growing literature has identified several conditions, including exporting, that contribute to plant survival. A prevailing sentiment suggests that anti-sweatshop activity against plants in developing countries adds the risk of making survival more difficult by imposing external constraints that may interfere with optimizing behavior. Using a relatively new plant-level panel dataset from Cambodia, this paper applies survival analysis to estimate the relationship between changes in working conditions and plant closure. The results find little, if any, evidence that improving working conditions increases the probability of closure. In fact, some evidence suggests that improvements in standards relating to compensation are positively correlated with the probability of plant survival.
Keywords: J8; J5; J3; 330; working conditions; apparel; sweatshops; plant survival; closure